2000
DOI: 10.1042/0264-6021:3520929
|View full text |Cite
|
Sign up to set email alerts
|

Rapid activation and partial inactivation of inositol trisphosphate receptors by adenophostin A

Abstract: Adenophostin A, the most potent known agonist of inositol 1,4, 5-trisphosphate (InsP(3)) receptors, stimulated (45)Ca(2+) release from the intracellular stores of permeabilized hepatocytes. The concentration of adenophostin A causing the half-maximal effect (EC(50)) was 7.1+/-0.5 nM, whereas the EC(50) for InsP(3) was 177+/-26 nM; both responses were positively co-operative. In rapid superfusion analyses of (45)Ca(2+) release from the intracellular stores of immobilized hepatocytes, maximal concentrations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Biphasic kinetics of Ca 2+ release rates in intact cells have been observed in many studies (reviewed in Bootman, 1994; Missiaen et al 1994; Parys et al 1996; Taylor, 1998), but either inactivation has been ruled out as a mechanism for release termination (Taylor & Potter, 1990; Oldershaw et al 1992; Hirose & Iino, 1994; Parys et al 1995; Combettes et al 1996; Beecroft & Taylor, 1997) or other types of mechanisms have been invoked (reviewed in Bootman, 1994; Missiaen et al 1994; Parys et al 1996; Taylor, 1998). In rapid perfusion protocols using isolated microsomes or permeabilized cells that attempted to maintain [InsP 3 ] and [Ca 2+ ] i constant, transient Ca 2+ release kinetics indicated that channel inactivation or partial inactivation played a role in the decay of release rates (Champeil et al 1989; Finch et al 1991 a ; Combettes et al 1994; Wilcox et al 1996; Dufour et al 1997; Marchant & Taylor, 1998; Adkins et al 2000), but questions have been raised regarding the efficacy of maintaining constant conditions in these protocols (Taylor, 1998). Observations of refractory periods following either global (Khodakhah & Ogden, 1995; Carter & Ogden, 1997; Ogden & Capiod, 1997) or more focal (Parker & Ivorra, 1990 a ; McCarron et al 2004) InsP 3 ‐mediated Ca 2+ release in intact cells are also consistent with channel inactivation in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biphasic kinetics of Ca 2+ release rates in intact cells have been observed in many studies (reviewed in Bootman, 1994; Missiaen et al 1994; Parys et al 1996; Taylor, 1998), but either inactivation has been ruled out as a mechanism for release termination (Taylor & Potter, 1990; Oldershaw et al 1992; Hirose & Iino, 1994; Parys et al 1995; Combettes et al 1996; Beecroft & Taylor, 1997) or other types of mechanisms have been invoked (reviewed in Bootman, 1994; Missiaen et al 1994; Parys et al 1996; Taylor, 1998). In rapid perfusion protocols using isolated microsomes or permeabilized cells that attempted to maintain [InsP 3 ] and [Ca 2+ ] i constant, transient Ca 2+ release kinetics indicated that channel inactivation or partial inactivation played a role in the decay of release rates (Champeil et al 1989; Finch et al 1991 a ; Combettes et al 1994; Wilcox et al 1996; Dufour et al 1997; Marchant & Taylor, 1998; Adkins et al 2000), but questions have been raised regarding the efficacy of maintaining constant conditions in these protocols (Taylor, 1998). Observations of refractory periods following either global (Khodakhah & Ogden, 1995; Carter & Ogden, 1997; Ogden & Capiod, 1997) or more focal (Parker & Ivorra, 1990 a ; McCarron et al 2004) InsP 3 ‐mediated Ca 2+ release in intact cells are also consistent with channel inactivation in intact cells.…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising because, with the steady-state ligand regulation of InsP 3 R channel P o discussed so far, it might have been expected that all InsP 3 R channels should become activated in response to sufficient agonist stimulation, releasing all of the InsP 3 -sensitive Ca 2ϩ stores, albeit at different rates depending on the agonist concentration. Time-dependent reduction in the rate of InsP 3 -mediated Ca 2ϩ release has been well-documented with flux assays (120,167,168,293) and fast perfusion protocols (5,82,91,120,140,293,513). Furthermore, the InsP 3 R has been observed to transform from a low-affinity, active state to a high-affinity, desensitized state (92,293).…”
Section: Ligand-dependent Insp 3 -Induced Insp 3 R Channel Inactimentioning
confidence: 92%
“…Furthermore, AdA is metabolically stable (190,334,448). Thus AdA has been applied as a metabolically stable InsP 3 substitute in studies of the InsP 3 R and its regulation (5,157,179,203,223,316,445,487), Ca 2ϩ release mediated by InsP 3 R (37, 292) and Ca 2ϩ entry due to depletion of intracellular Ca 2ϩ stores (60,107,160,172,193,265). Investigations into the InsP 3 R binding affinity and biological activity of AdA and its analogs have also provided insights into the structural determinants for ligand interactions with the InsP 3 binding site of the channel (51,93,332).…”
Section: H Activation Of Insp 3 R Channel By Adenophostin and Its Anmentioning
confidence: 99%
“…Activity was typically evident 3–5 min after establishing the whole cell configuration at 1 μ m InsP 3 , but occurred essentially immediately following breakthrough with 100 μ m InsP 3 in the pipette. In a similar fashion, channel activity occurred immediately when the pipette solution contained the high affinity InsP 3 R agonist, adenophostin A (ADO) (Adkins et al 2000). A gravity fed multibarrelled glass perfusion pipette was used for local bath exchange during forskolin experiments.…”
Section: Methodsmentioning
confidence: 98%